Objective Estimates Improve Risk Stratification for Primary Graft Dysfunction after Lung Transplantation - Shah, R. J.; Diamond, J. M.; Cantu, E.; Flesch, J.; Lee, J. C.; Lederer, D. J.; Lama, V. N.; Orens, J.; Weinacker, A.; Wilkes, D. S.; Roe, D.; Bhorade, S.; et al. (American journal of transplantation, 2015)
Primary graft dysfunction (PGD) is a major cause of early mortality after lung transplant. We aimed to define objective estimates of PGD risk based on readily available clinical variables, using a prospective study of 11 centers in the Lung Transplant Outcomes Group (LTOG). Derivation included 1255 subjects from 2002 to 2010; with separate validation in 382 subjects accrued from 2011 to 2012. We used logistic regression to identify predictors of grade 3 PGD at 48/72 h, and decision curve methods to assess impact on clinical decisions. 211/1255 subjects in the derivation and 56/382 subjects in the validation developed PGD. We developed three prediction models, where low‐risk recipients had a normal BMI (18.5–25 kg/m2), chronic obstructive pulmonary disease/cystic fibrosis, and absent or mild pulmonary hypertension (mPAP<40 mmHg). All others were considered higher‐risk. Low‐risk recipients had a predicted PGD risk of 4–7%, and high‐risk a predicted PGD risk of 15–18%. Adding a donor‐smoking lung to a higher‐risk recipient significantly increased PGD risk, although risk did not change in low‐risk recipients. Validation demonstrated that probability estimates were generally accurate and that models worked best at baseline PGD incidences between 5% and 25%. We conclude that valid estimates of PGD risk can be produced using readily available clinical variables. Using three clinical prediction models based on recipient and donor factors for the development of primary graft dysfunction (PGD) after lung transplantation, the authors demonstrate that elevated mean pulmonary arterial pressures, a diagnosis other than cystic fibrosis or chronic obstructive pulmonary disease, and obesity define high‐risk recipients, and addition of a lung from a smoking donor significantly increases PGD risk in the high‐risk group.